Sex-Specific Differences in the Physiological and Biochemical Performance of Arbuscular Mycorrhizal Fungi-Inoculated Mulberry Clones Under Salinity Stress - Wang, Yan-Hong; Zhang, Nai-Li; Wang, Min-Qiang; He, Xiao-Bin; Lv, Zhi-Qiang; Wei, Jia; Su, Xiu; Wu, Ai-Ping; Li, Yan (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungi (AMF) are often considered bioameliorators. AMF can promote plant growth under various stressful conditions; however, differences between male and female clones in mycorrhizal strategies that protect plants from the detrimental effects of salinity is not well studied. In this study, we aimed to examine the interactive effects of salinity and AMF on the growth, photosynthetic traits, nutrient uptake and biochemical responses of Morus alba males and females. In a factorial setup, male and female M. alba clones were subjected to three salinity regimes (0, 50, and 200 mM NaCl) and planted in soil with or without Funneliformis mosseae inoculation. The results showed that NaCl alone conferred negative effects on the growth, salinity tolerance, photosynthetic performance, and shoot and root ionic ratios (K+:Na+, Ca2+:Na+, and Mg2+:Na+) in both sexes; in contrast, mycorrhizal inoculation mitigated the detrimental effects of salinity. Furthermore, the mycorrhizal effects were closely correlated with Mn2+, proline, and N concentrations. Females benefited more from AMF inoculation as shown by the enhancements in their biomass accumulation, and N, proline, K+, Mg2+, Fe2+, Zn2+, and Mn2+ concentrations than males with mycorrhizal inoculation under saline conditions. In comparison, male plants inoculated with AMF showed improvements in the biomass allocated to the roots, P and POD concentrations under saline conditions. These sex-specific differences suggest that male and female mulberry clones adopted different mycorrhizal strategies when growing under saline conditions. Overall, our results provide insight into the sex-specific difference in the performance of AMF-associated mulberry clones, suggesting that female mulberry could be more suitable for vegetation remediation than the male one, owing to the higher salinity tolerance capacity of female plants.